2002
DOI: 10.1530/reprod/124.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high concentrations of hyaluronan in culture medium on development and survival rates of fresh and frozen-thawed bovine embryos produced in vitro

Abstract: Hyaluronic acid (HA) is the main glycosaminoglycan present in follicular, oviductal and uterine fluids. The main functions of HA include dynamic processes that are mediated through interaction with extracellular matrix components, regulation of gene expression, cell proliferation and cell differentiation. HA increases the viscosity of solutions and also has several physiological functions, including regulation of water distribution and waterbinding capacity. The addition of 6 mg HA ml-1 to synthetic oviduct fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
(25 reference statements)
0
26
0
1
Order By: Relevance
“…It is involved in several processes mediated through interaction with matrix components, cell proliferation, and cell differentiation [35]. Hyaluronan and its receptors are thought to be involved in the regulation of GFs [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in several processes mediated through interaction with matrix components, cell proliferation, and cell differentiation [35]. Hyaluronan and its receptors are thought to be involved in the regulation of GFs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it has been demonstrated that hyaluronan has an important role in embryo culture media. Hyaluronan can substitute for albumin in culture media but what is perhaps more significant for human IVF applications is that the addition of hyaluronan to a culture medium containing albumin significantly increased development but also improved the cryosurvival of embryos [22,23]. In addition, recent randomized controlled trials in clinical IVF confirmed that elevating the levels of hyaluronan increased pregnancy and implantation rates, which was particularly evident in selected patient groups [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…1) which is probably due to the presence of hyaluronic acid (HA) in the second step and different growth factors such as LIF, insulin-like growth factor-II (IGF-II), and transforming growth factor b (TGFb) in BRL-medium (Stojkovic et al 1995). HA plays a very important role in early embryogenesis (Stojkovic et al 2003) and, when added to culture medium, HA increases the cell number of mouse (Gardner et al 1999, Figueiredo et al 2002 and bovine blastocysts (Stojkovic et al 2002). Added to serum-free medium, LIF increases the blastocyst rate, hatching rate and cell number of mammalian preimplantation embryos (Fry 1992, Dunglison et al 1996 but whether greater numbers of ICM cells in day 8 blastocysts allow more-efficient derivation of hES cells is difficult to say.…”
Section: What Is Important For the Derivation Of Hes Cells?mentioning
confidence: 99%